STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN MARKET SHARE SEGMEN REMAJA PT TELKOMSEL DI KOTA SURABAYA - Agustin, Deliana Putri (representamen, 2017)
Deliana Putri Agustin, Marketing Communication Strategy In Improving Market Share YouthSegment PT Telkomsel in Surabaya City. This study aims to describe the marketing communicationstrategy conducted by PT Telkomsel in increasing the market share in Segment Youth based on kotlertheory (1976: 46) which is Marketing Mix consisting of Four P (4P) ie product, price, place, place),and promotion (promotion) and AIDDA Theory (Attention, Interest, Desire, Decision, Action). Thetype of this research is descriptive qualitative, that is descriptive research which describes factfactually and meticulously as well as qualitative research which yields findings that can not beobtained by statistic or measurement. This research describes marketing communication strategyconducted by PT Telkomsel assisted by SPV Youth and Community Telkomsel Branch Surabya,covering product (product), price (price), place (place), and promotion (promotion). Data collectedthrough in-depth interviews SPV Youth and Community Branch Surabaya as representative of PTTelkomsel as Key Informant and some staff as informant as well as to test the validity of data. Theresult of the research shows that the fourth communication strategy conducted by PT Telkomsel inincreasing the market share of youth segment is by promotion.Keywords : Marketing Communication Strategy